Educational policies and the gender gap in test scores: A cross-country analysis - Zoltán Hermann; Marianna Kopasz (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2018)
Girls tend to outperform boys in reading tests, while they usually lag behind boys in math. However, the size of the gender gap varies to a great extent between countries. While the existing literature explains these differences as being mainly due to cultural factors, this paper explores whether this cross-country variation is related to educational policies like tracking, grade retention, and individualised teaching practices. The gender test score gap is analysed in math, reading and science using the PISA 2012 dataset. Multilevel models are used in the estimation. The results suggest that the extent of the gender gap is indeed associated with certain characteristics of the various education systems. First, applying a difference-in-differences estimation method, it was found that early tracking has a direct effect on the gender gap in test scores, in favour of girls. Second, suggestive evidence shows that more student-oriented teaching practices also benefit girls relative to boys, both between and within countries, and within schools. Finally, grade retention is correlated with the gender gap, though there is further evidence suggesting that this correlation is very unlikely to represent a causal effect.
Keywords: I21; J24; 330; Gender stratification; tracking; grade retention; teaching practice; PISA; multilevel model; difference-in-differences